Reimagining school leadership : sustaining improvement through and beyond uncertainty - DeMatthews, David E.; Kruse, Sharon D. (Emerald Publishing Limited, 2024)
School leadership is critical to advancing student achievement and other educational equity initiatives, but contemporary approaches to leadership and improvement are increasingly insufficient in a rapidly changing and increasingly unpredictable world. With a focus on kindergarten through to twelfth grade schools, Reimagining School Leadership critically considers current conceptions of school leadership and school improvement throughout the U.S. and around the world. The chapters focus on leading through uncertainty, building sustainability, and advancing student experiences and outcomes beyond narrow quantitative outcome measures such as test scores, graduation rates and college admission rates. Reimagining School Leadership challenges the limits of traditional approaches to instructional leadership by considering historical and contemporary problems confronting school leaders, the successes and shortcomings of current leadership and improvement approaches and suggest ways to reimagine school leadership through emerging leadership theories and their applicability to school leaders.
Keywords: Educational leadership.; Education -- Leadership.; Educational administration and organization.; Educational strategies and policy.; elektronické knihy; electronic books